Geophysical, Sedimentological and Geochemical Data from the Lower Havel Inner Delta (Gülpe Island), Brandenburg (Germany) - Anne Köhler; Marco Pohle; Matteo Bauckholt; Susann Birnstengel; Marie Kaniecki; Birgit Schneider; Ulrike Werban; Christoph Zielhofer (PANGAEA, 2025)
To investigate subsurface features in the Lower Havel River floodplain, we conducted Electrical Resistivity Tomography (ERT) transects and Electromagnetic Induction (EMI) surveys at three different depths in 2023 and 2024. These near surface geophysical methods were complemented by 24 driving core drillings to relate the electrical properties with sedimentological characteristics. Additionally, five selected sediment cores were used for subsequent geochemical lab analyses (grain size, CNS, TOC, TIC). Electromagnetic induction (EMI) was measured with a CMD-Mini Explorer (GF Instruments s.r.o., Brno, Czech Republic) in June 2023 and June 2024. We used the vertical dipole (VDP) at coil spacings of 0.32 m (VDP1), 0.71 m (VDP2) and 1.18 m (VDP3), archieving effective penetration depths of 0.5 m (VDP1), 1.0 m (VDP2) and 1.8 m (VDP3). According to the manufacturer, 70% of the signal originate from above these depths. The EMI sensors measure the apparent electrical conductivity (ECa, in mS/m). Measurements were taken by carrying the instrument about 0.2 m above ground while being directly connected to D-GPS (Leica GPS1200) for positioning. The acquisition rate was five measurements per second. Data quality was checked by measuring a reference line before and after each measurement. The area investigated by EMI in June 2023 is located to the north and northeast of the Gülpe research station. It has a total area of 12.3 ha. The reference line was located in the southern part of the study area. No drift correction had to be applied due to good data quality. Reference lines and single outliers were removed. The area investigated by EMI in June 2024 is located southeast of the research station. The survey area there is 8.1 ha in size. The reference line for the measurements there was located in the north-westernmost area of the site. No drift correction had to be applied due to good data quality. Reference lines and single outliers were removed. The Electrical Resistivity Tomography (ERT) data were acquired by using a PC controlled DC resistivity meter system (RESECS, Geoserve, Kiel, Germany). In total, we measured four ERT transects. Two transects in June 2023, where transect 1 had a total length of 259 m with an electrode spacing of 0.5 m and transect 2 had a total length of 223 m with an electrode spacing of 1 m. The measurements in 2023 were carried out under extreme dry conditions. Two further transects were measured in June 2024 with an electrode spacing of 1m, transect 3 with a total length of 207 m and transect 4 with a total length of 239 m. We applied wenner alpha and dipol-dipol configuration. The coordinates and the height of the electrodes were measured with a D-GPS (2023: TOPCON HiPer II / 2024: Leica GPS1200). Sediment cores were recovered using a hand-held Cobra Pro (Atlas Copco) core drilling system with a 60 mm diameter open corer. One-meter segments were retrieved and assessed in the field for sedimentological features, including estimations of grain size, carbonate content, humus content, and redox features (AG Boden 2005, 2024). Colour descriptions were carried out using the Munsell Soil Color Chart. The exact positions of the drilling points were recorded using a differential GPS device (TOPCON HiPer II). The cores were photographed, documented and sampled at 5–10 cm intervals for subsequent laboratory analyses. Bulk samples from five selected cores (RK1, RK3, RK13, RK15, RK17) were freeze-dried, sieved (2 mm), and weighed. Total carbon (TC), total nitrogen (TN), and total sulfur (TS) contents were measured using a CNS analyzer (Vario EL cube, Elementar). Inorganic carbon (TIC) was determined using calcimeter measurements (Scheibler method, Eijkelkamp). Organic carbon (TOC) was calculated as TOC = TC - TIC. For the grain size analyses, sediment samples were first sieved to <2 mm and subsamples of 10 g were treated with 50 ml of 35% hydrogen peroxide (H?O?) and gently heated to remove organic matter. Following this, 10 ml of 0.4 N sodium pyrophosphate solution (Na?P?O?) was added to disperse the particles, and the suspension was subjected to ultrasonic treatment for 45 minutes. The sand fraction was analysed by dry sieving and classified into four size classes: coarse sand (2000–630 μm), medium sand (630–200 μm), fine sand (200–125 μm), and very fine sand (125–63 μm). Finer fractions were determined using X-ray granulometry (XRG) with a SediGraph III 5120 (Micromeritics). These included coarse silt (63–20 μm), medium silt (20–6.3 μm), fine silt (6.3–2.0 μm), coarse clay (2.0–0.6 μm), medium clay (0.6–0.2 μm), and fine clay (<0.2 μm).